2018
DOI: 10.1155/2018/1391387
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Intercellular Signalling Mechanisms following DNA Damage Are Modulated By PINK1

Abstract: Impaired mitochondrial function and accumulation of DNA damage have been recognized as hallmarks of age-related diseases. Mitochondrial dysfunction initiates protective signalling mechanisms coordinated at nuclear level particularly by modulating transcription of stress signalling factors. In turn, cellular response to DNA lesions comprises a series of interconnected complex protective pathways, which require the energetic and metabolic support of the mitochondria. These are involved in intracellular as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Mitochondrial function modulated by HtrA2 and ISR appears to have a role in the different pathways controlling the nuclear DNA stability. In a previous study, our group found evidence of increase in DNA damage due to mitochondrial PINK1 loss of function [ 19 ]. Thus, disruption of mitochondrial homeostasis at various levels appears to have essentially the same end result of enhancing genotoxic damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial function modulated by HtrA2 and ISR appears to have a role in the different pathways controlling the nuclear DNA stability. In a previous study, our group found evidence of increase in DNA damage due to mitochondrial PINK1 loss of function [ 19 ]. Thus, disruption of mitochondrial homeostasis at various levels appears to have essentially the same end result of enhancing genotoxic damage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, following the IR-hitting cytoplasm, the ER mass increased; further, when the cells were treated with rotenone together with depressing the ER chaperone BiP, the MN level increased [ 21 ]. We have also shown that mitochondrial dysfunction through PINK1 loss of function (in directly and bystander genotoxic treated cells) impairs both intracellular and intercellular bystander signalling [ 19 ]. Thus, similarly with the induction of direct genotoxic damage, disruption of mitochondrial homeostasis at various levels appears to have essentially the same end result of impairing bystander signalling.…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial PTEN-induced kinase PINK1 is implicated in retrograde signaling pathways to the nucleus in response to genotoxic stress. This signaling involves altered reactive oxygen species patterns and ATP production and triggers nuclear responses for maintaining cellular homeostasis ( 205 ). A unique form of retrograde mitochondrial signaling requires MOTS-c, a regulatory peptide encoded as a short ORF within the mitochondrial 12S rRNA gene.…”
Section: Regulation Of Mitochondrial Transcriptionmentioning
confidence: 99%
“…Autophosphorylation on residues Ser228, Thr257 and Ser402 of the C‐terminal domain of PINK1 occurs, which activates PINK1 (Aerts, Craessaerts, De Strooper, & Morais, 2015; Okatsu, Oka, et al, 2012), to form a high molecular weight complex, triggering a chain of events ultimately resulting in PINK1/Parkin‐mediated mitophagy, that is the selective breakdown of damaged mitochondria via autophagy (Okatsu et al., 2013). Based on a number of studies, ubiquitin (Ub) appears to be the primary substrate of PINK1 that is not imported into the IMM (Kane et al., 2014; Kazlauskaite et al., 2014; Koyano et al, 2014; Okatsu, Kimura, Oka, Tanaka, & Matsuda, 2015; Okatsu, Koyano, et al, 2015; Okatsu et al, 2018; Rasool et al 2018; Temelie, Savu, & Moisoi, 2018). PINK1/Parkin‐mediated autophagy is initiated by the loss of mitochondrial membrane potential, which leads to the localization of PINK1 to the OMM and recruitment of Parkin as observed in Drosophila , rodents, as well as HeLa and HEK293 cells.…”
Section: Genetic Evidence To Support Mitochondria As Central To Pd Pa...mentioning
confidence: 99%